2020
DOI: 10.3390/molecules25112665
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-Pressure Processing on Physicochemical Properties and Sensory Characteristics of Three Different Lamb Meat Cuts

Abstract: This study investigated the effects of high pressure processing (HPP) on the physicochemical properties and sensory characteristics of different lamb meat cuts. Lamb meat discolouration occurred when HPP was applied at 400 and 600 MPa. Thiobarbituric acid reactive substances (TBARS) values significantly increased with pressure increase from 200 to 600 MPa for loin cut, and 300 to 600 MPa for shoulder and shank cuts. Saturated fatty acid and polyunsaturated fatty acid content significantly decreased with pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Bolar, eye of loin and tenderloin cuts were significantly lower in SFA, MUFA, and PUFA content at higher pressure treatments, as compared to control ( Table 1 ). A significant decrease in the fatty acids in the loin cut as compared to shank and shoulder cuts of lamb at higher pressures has also been observed by Ma et al [ 40 ]. This reduction can be attributed to the increased oxidation and acidification of the fatty acids at higher pressures.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Bolar, eye of loin and tenderloin cuts were significantly lower in SFA, MUFA, and PUFA content at higher pressure treatments, as compared to control ( Table 1 ). A significant decrease in the fatty acids in the loin cut as compared to shank and shoulder cuts of lamb at higher pressures has also been observed by Ma et al [ 40 ]. This reduction can be attributed to the increased oxidation and acidification of the fatty acids at higher pressures.…”
Section: Resultssupporting
confidence: 63%
“…With respect to individual fatty acids, a significant decrease in PUFAs at high pressure was mainly associated with changes in C18:2n-6 and C18:3n-3. Similarly, Ma et al [ 40 ] found that total PUFA content was significantly lower at 200 and 300 MPa in shank and shoulder cuts of lamb compared to control samples. The authors associated this decrease in PUFA content with changes in C18:2n-6 and C18:3n-3 fatty acid content.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The meat treated with HPP at high pressure levels of 400 and 600 MPa were associated with browned, livery, and oxidized flavors [ 25 ], which will have an impact on the consumer and market behavior of the product. There is no immediate effect of HPP on the oxidative stress of meat [ 26 ].…”
Section: Processingmentioning
confidence: 99%